Analisis User Experience (UX) Pada Aplikasi Game Clash Of Clans Menggunakan Metode User Experience Questionnaire (UEQ) - AlHafiidh, Agung; Oktadini, Nabila Rizky (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 8 No 2 (2023): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Desember 2023)DO - 10.51211/isbi.v8i2.2694, 2023)
Information technology is currently developing very rapidly and meets people's needs to make work easier, fulfill entertainment needs, and even fulfill sports needs among people in the era of the industrial revolution generation 4.0. What is currently popular is Clash of clans or better known as "CoC". One game that is quite popular among young people. Based on 54.9 million reviews on Android devices and 2.3 million reviews on iOS devices, it still gets negative reviews from CoC users themselves who are not satisfied with the features or security of the game itself. From the problems above, a User Experience (UX) evaluation can be carried out using the User Experience Questionnaire (UEQ) method, which is an analysis of user experience reviews in order to improve the quality of the game based on six different variables. The review was carried out by distributing an online questionnaire in the form of a Google form consisting of 26 questions and succeeded in collecting 105 respondents. Then, after the analysis was carried out, it was concluded that all aspects of the Clash Of Clans game application received positive evaluation values, namely with a mean value > 0.8 starting from the aspects of Attractiveness, Perspicuity, Efficiency, Dependabilit(Accuracy), Stimulation (Stimulation), and Novelty (Novelty). However, in the Dependability aspect, one of the indicators has a neutral evaluation value, namely the indicator can be predicted or cannot be predicted. This is influential because the resulting mean value is based on the benchmark results graph, namely "below avarege". Based on the analysis that has been carried out on the Clash of Clans game, it can be concluded that in using this application some users are satisfied, but there needs to be improvements to this game by providing more sophisticated security features and providing continuous innovation.